Принципы управления контурной динамической системой измерения магнитного момента при угловом перемещении технического объекта - Крамчанин, Е. Г. (НТУ "ХПИ", 2011)
Рассмотрены принципы управления контурными динамическими системами измерения магнитного момента при угловом перемещении технического объекта. Рассмотрена функциональная схема управления системой и особенности ее практической реализации.

Principles of control are formulated for the planimetric dynamic system intended for measuring of magnetic moment in technical objects at their turning movement. The function chart of the system and features of its practical realization are discussed.
Principles of control in the planimetric dynamic system intended for measing of magnetic moment in technical objects at their turning movement
Keywords: ММ; ТО; магнитная сигнатура; измерительный контур; technical object; magnetic moment; measurement